"GYNECOLOGICAL" HERNIA: A CASE OF ACUTE ABDOMEN CAUSED BY A PINCHED ADENOMYOMA (CLINICAL OBSERVATION) - Karelina, Olga Borisovna; Bolotova, Svetlana Nikolaevna; Bolotov, Konstantin Sergeevich; Ivanov, Andrey Viktorovich (Mother and Baby in Kuzbass, 2026)
The differential diagnosis of acute abdominal syndrome in gynecology includes a number of life-threatening conditions. Of particular difficulty are extremely rare causes, such as pinching of the myomatous or adenomyomatous node in the inguinal canal, which can mimic both surgical and gynecological pathology. The final diagnosis is often established intraoperatively, which confirms the need for emergency surgery as the main method of diagnosis and treatment. The organ-preserving approach is an effective tactic for patients of reproductive age. A mandatory final stage is a pathohistological examination.